Communicating with Northerners on the absence of SARS-CoV-2 in migratory snow geese. Issue 3 (2nd October 2021) - Frederick, Christina; Girard, Catherine; Wong, Gary; Lemire, Mélanie; Langwieder, Alexandra; Martin, Marie-Claude; Legagneux, Pierre
ABSTRACT: The COVID-19 pandemic has raised many concerns among Indigenous communities about virus transmission risks from wild food, particularly migratory birds. Snow geese contribute significantly to food security in Indigenous contexts, which is precarious in many communities. The risk to goose hunters is very unlikely as coronaviruses found in birds are from different genera than that of SARS-CoV-2, the etiologic agent responsible for COVID-19. Nevertheless, little is currently known about the host tropism range of SARS-CoV-2. To address the concerns raised by Northern communities, we captured 500 snow geese in May 2020 at their stopover along the St Lawrence estuary. We took oropharyngeal and cloacal samples before releasing the birds. All samples were tested for SARS-CoV-2 within one week and were found to be PCR-negative, allowing us to communicate rapidly with Northern communities. The current pandemic has shown that the importance of understanding animals as potential viral reservoirs, and that a better understanding of these viruses will better prepare us for future spillover events. This project demonstrates that researchers can be quickly and efficiently mobilized to respond to concerns from Indigenous communities.